Belize. Significant achievements 2010 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Belize during 2010 are identified, with respect to the needs and interests of the country, strengthening issues such as leadership, biosecurity, agrotourism, rural development, organic agriculture, public policies, post-harvest technology, training, inclusion youth and in the corn and bean value chains.